Intellectual property rights, technology diffusion, and agricultural development: Cross-country evidence - Spielman, David J.; Ma, Xingliang (International Food Policy Research Institute, 2014)
The role of intellectual property rights (IPRs) has been extensively debated in the literature on technology transfers and agricultural production in developing countries. However, few studies offer cross-country evidence on how IPRs affect yield growth, for example, by incentivizing private-sector investment in cultivar improvement. We address this knowledge gap by testing technology diffusion patterns for six major crops using a unique dataset for the period 1961–2010 and an Arellano–Bond linear dynamic panel-data estimation approach. Findings indicate that both biological and legal forms of IPRs tend to promote yield gap convergence between developed and developing countries, although effects vary between crops.